Continuity and change in human rights appropriation: The case of Turkey - Çalı, Başak; Demir-Gürsel, Esra (Icon-International Journal of Constitutional Law, 2023)
This article analyzes the political and legal dynamics of continuity and change in the appropriation of human rights in Turkey against the backdrop of growing authoritarian practices. Human rights appropriation in Turkey has traditionally focused on the interpretation of human rights favoring national security and secular sensibilities to determine who has human rights and to what extent. The recent decade is a case of continuity and change. While the secularist frame has been replaced by a religious frame defining authentic human rights holders as members of the “pious” Turkish Muslim family and society, the national security frame has remained a continuous source of human rights appropriation. The article first offers an account of the dynamics of old forms of human rights appropriation in Turkey. It then analyzes the new actors, strategies, and transnational dimensions of new forms of human rights (mis)appropriation.
CRIS-Team Scopus Importer:2024-06-28